2020
DOI: 10.1155/2020/8849666
|View full text |Cite
|
Sign up to set email alerts
|

Mining-Induced Stress-Fissure Field Evolution and the Disaster-Causing Mechanism in the High Gas Working Face of the Deep Hard Strata

Abstract: The compound dynamic disaster of coal and gas outbursts and rockburst is a typical hazard jeopardizing the mining of the high gas content coal seam under a hard roof condition. In this study, the hard roof’s mechanism inducing this hazard is analyzed. Physical analog modeling experiments and in situ monitoring of mining-induced stress were performed during coal seam mining under a hard roof condition. The pattern of hard roof breakage effect on the stress-fissure field evolution was revealed. The elastic energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In terms of mining disaster analysis under thick hard roof conditions and by the investigation and measurement of the ground pressure in the working face with a thick hard roof, it is concluded that a phenomenon of the strong ground pressure exists in the working face with a thick hard roof, a large number of elastic properties are accumulated in the thick and hard rock itself with the coal and rock volume under it, and the mining instability of the thick hard roof has a hidden danger of inducing rock burst and air blast disaster in the working face (Christopher and Michael, 2016;Iannacchione and Tadolini, 2016;Tan et al, 2019). Through the analysis of the stope ground pressure behavior under thick hard roof conditions, it is revealed that the instability of the thick and hard rock structure in a large space stope leads to the strong ground pressure behavior of the working face, and the classification evaluation model of the ground pressure strength is established to guide the prediction and pre-control of the ground pressure disaster in hard roof coal seam mining (Xia et al, 2017;Dou et al, 2020;Gao et al, 2020). Some scholars have carried out microseismic monitoring of the overlying rock of the stope under thick hard roof conditions, analyzed the vibration response of the mining fracture of the overlying rock of the stope, and revealed the elastic release and propagation characteristics of its accumulation caused by the mining fracture of the thick and hard roof (Lu et al, 2015;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of mining disaster analysis under thick hard roof conditions and by the investigation and measurement of the ground pressure in the working face with a thick hard roof, it is concluded that a phenomenon of the strong ground pressure exists in the working face with a thick hard roof, a large number of elastic properties are accumulated in the thick and hard rock itself with the coal and rock volume under it, and the mining instability of the thick hard roof has a hidden danger of inducing rock burst and air blast disaster in the working face (Christopher and Michael, 2016;Iannacchione and Tadolini, 2016;Tan et al, 2019). Through the analysis of the stope ground pressure behavior under thick hard roof conditions, it is revealed that the instability of the thick and hard rock structure in a large space stope leads to the strong ground pressure behavior of the working face, and the classification evaluation model of the ground pressure strength is established to guide the prediction and pre-control of the ground pressure disaster in hard roof coal seam mining (Xia et al, 2017;Dou et al, 2020;Gao et al, 2020). Some scholars have carried out microseismic monitoring of the overlying rock of the stope under thick hard roof conditions, analyzed the vibration response of the mining fracture of the overlying rock of the stope, and revealed the elastic release and propagation characteristics of its accumulation caused by the mining fracture of the thick and hard roof (Lu et al, 2015;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have made many significant achievements in the study of coal rock gas dynamic disasters [8][9][10][11], to make people have a certain degree of understanding of the mechanism of coal rock gas dynamic disasters, in which the comprehensive action hypothesis [12,13] indicated that the increase of gas pressure would reduce the threshold of coal strength when coal and gas outburst occurred. Former Soviet scientist Pethuoff first proposed the concept of impact-outstanding unified research.…”
Section: Introductionmentioning
confidence: 99%
“…Thick and hard rock strata (THRS) exist widely in coal measure strata, which control the movements of overlying rock strata in stopes because of the great thickness, hardness, and integrity. In case of THRS failure and instability, huge elastic energy is released and transmitted to the stopes, which aggravates the risk of coal and rock dynamic disasters (Figure 1) [9,10].…”
Section: Introductionmentioning
confidence: 99%